2020
DOI: 10.1111/liv.14505
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of FGF9 with FGFR3‐IIIb/IIIc, a putative driver of growth and aggressive behaviour of hepatocellular carcinoma

Abstract: Background & Aims Recently, overexpression of the fibroblast growth factor receptor 3 (FGFR3) splice variants FGFR3‐IIIb and FGFR3‐IIIc was found in ~50% of hepatocellular carcinoma (HCC). Here, we aim to identify FGFR3‐IIIb/IIIc ligands, which drive the progression of HCC. Methods FACS, MTT assay and/or growth curves served to identify the FGFR3‐IIIb/IIIc ligand being most effective to induce growth of hepatoma/hepatocarcinoma cell lines, established from human HCC. The most potent FGF was characterized regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Regarding its potential as therapeutic target, it is of particular interest that several studies have shown that FGF9 plays a detrimental role in HCC progression. [102][103][104]…”
Section: Fgf9 Subfamilymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding its potential as therapeutic target, it is of particular interest that several studies have shown that FGF9 plays a detrimental role in HCC progression. [102][103][104]…”
Section: Fgf9 Subfamilymentioning
confidence: 99%
“…9 In contrast, freshly isolated HSC do not express FGFR3B but FGFR3C, 92 and FGFR3C is upregulated in TGFβ treated LX2 cells. 132 Although FGFR3 plays an important role in HCC development and progression 9,103,137 and FGFR3 expression is elevated in human cirrhotic livers, 132 the functional role of FGFR3 and its isoforms has not yet been investigated in the context of hepatic fibrosis. A recent study revealed that FGF9-activated FGFR3 promoted fibrosis in systemic sclerosis through activation of profibrotic signalling pathways.…”
Section: Fibroblast Growth Factor Receptormentioning
confidence: 99%
“…FGF9 expression is often co-upregulated with FGFR3 IIIb/IIIc expression in HCC patients. Furthermore, FGF9 is the most dominant ligand for FGFR3 IIIb/IIIc in HCC [ 32 ]. FGF9 is secreted mainly by HSCs in normal and cirrhotic livers and acts by the paracrine mechanism to stimulate tumor cells.…”
Section: Deregulation Of Fgf/fgfr In Hccmentioning
confidence: 99%
“…However, both findings emphasize the tumorigenic role of FGF9 in HCC. FGF9 exerts its tumorigenic role by specifically binding to FGFR3, facilitating the proliferation and migration of HCC cell lines and promoting new blood and lymphatic capillary formation [ 32 ]. Moreover, FGF9 is involved in sorafenib resistance, indicating that FGF9 may be a promising target of HCC.…”
Section: Deregulation Of Fgf/fgfr In Hccmentioning
confidence: 99%
See 1 more Smart Citation